Mudanças no perfil socioeconômico e ambiental provocadas pela atividade turística no município de Guaramiranga-CE. - Teixeira, Ana Lúcia Gomes de Freitas (2005)
This M-Sc Thesis, whose title is “Changes in the socioeconomic and environmental profile from tourist activity in the municipal district of Guaramiranga-Ce”, has main objective to accomplish a study about changes in the socioeconomic and environmental profile caused by the actions tourist activites in Guaramiranga. It is used as method for obtaining data, individual, secret and anonymous, through questionnaire with closed and open questions, accomplished in the municipal, accompanied of participant observation in having referred place. The analysis and interpretation of the primary and secondary data demonstrate that the tourism has been contributing to the socioeconomic development of the municipal in a gradual way. Guaramiranga still protects traditional production processes that base on flowers, vegetables, fruits and craft. Now, beginning to a new format in their production way with the increment of the tourist activity, generating occupation and income for the population and the local trade. Consequently the speculators appear, constructions of residences and of equipments of lodging means and of infrastructure. In most of cases, speculation propitiates actions causadrs antropc of significant damages to the natural environment, committing the sustainability of the tourism in the city of Guaramiranga.